A multidisciplinary definition of privacy labels. (20th April 2022) - Johansen, Johanna; Pedersen, Tore; Fischer-Hübner, Simone; Johansen, Christian; Schneider, Gerardo; Roosendaal, Arnold; Zwingelberg, Harald; Sivesind, Anders Jakob; Noll, Josef
Abstract : Purpose: This paper aims to present arguments about how a complex concept of privacy labeling can be a solution to the current state of privacy. Design/methodology/approach: The authors give a precise definition of Privacy Labeling (PL), painting a panoptic portrait from seven different perspectives: Business, Legal, Regulatory, Usability and Human Factors, Educative, Technological and Multidisciplinary. They describe a common vision, proposing several important "traits of character" of PL as well as identifying "undeveloped potentialities", i.e. open problems on which the community can focus. Findings: This position paper identifies the stakeholders of the PL and their needs with regard to privacy, describing how PL should be and look like to address these needs. Main aspects considered are the PL's educational power to change people's knowledge of privacy, tools useful for constructing PL and the possible visual appearances of PL. They also identify how the present landscape of privacy certifications could be improved by PL. Originality/value: The authors adopt a multidisciplinary approach to defining PL as well as give guidelines in the form of goals, characteristics, open problems, starting points and a roadmap for creating the ideal PL.